Propranolol-Loaded Trehalosome as Antiproliferative Agent for Treating Skin Cancer: Optimization, Cytotoxicity, and In Silico Studies - Mona K. Younis; Yara E. Elakkad; Rasha R. Fakhr Eldeen; Isra H. Ali; Islam A. Khalil (MDPI AG, 2023)
This study aims at preparing propranolol-loaded trehalosomes (a trehalose-coated liposome) to be used as an antiproliferative agent for treating skin cancer. A factorial design was used to select the optimum formula, where trehalose, lecithin, and Tween 80 levels were studied. A total of 24 runs were prepared and characterized according to size, charge, entrapment efficiency, and release after 3 h to select the optimum formula. The optimized formula was investigated using TEM, DSC, and FTIR. Cell studies were carried out against the human melanoma cell line to measure cytotoxicity, apoptosis/necrosis, and cell cycle arrest. In silico studies were conducted to understand the interaction between propranolol and the influential receptors in melanoma. The results showed the selected formula consisted of trehalose (175 mg), lecithin (164 mg), and Tween 80 (200 mg) with a size of 245 nm, a charge of −9 mV, an EE% of 68%, and a Q3 of 62%. Moreover, the selected formula has good cytotoxicity compared to the free drug due to the synergistic effect of the drug and the designed carrier. IC50 of free propranolol and the encapsulation of propranolol were 17.48 μg/mL and 7.26 μg/mL, respectively. Also, propranolol and the encapsulation of propranolol were found to significantly increase early and late apoptosis, in addition to inducing G1 phase cell cycle arrest. An in silico virtual study demonstrated that the highest influential receptors in melanoma were the vitamin D receptor, CRH-R1, VEGFR 1, and c-Kit, which matches the results of experimental apoptotic and cell cycle analysis. In conclusion, the selected formula has good cytotoxicity compared to the free drug due to the synergistic effect of the drug and the designed carrier, which make it a good candidate as an antiproliferative agent for treating skin cancer.